The Effect of Range of Motion (ROM) Application on Muscle Strength in Elderly Stroke Sufferers at the Tresna Werdha Asisi Social Institute Sukabumi City the Year 2022 - Hotmarida Silalahi; Siti Fatimah; Lina Tri Nurjanah; Wita Yuni Suwandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
A stroke is a brain dysfunction that occurs suddenly due to abnormal blood circulation in the brain. An elderly is someone who has entered the age of 60 years and over. Muscle strength is the strength of a muscle or muscle group produced to fight resistance with maximum effort. Range Of Motion (ROM) is an exercise performed to maintain or improve the ability to move joints normally and completely to increase muscle mass and tone to prevent deformities, stiffness, and contractures